Analisis Pengaruh Tata Ruang Kantor terhadap Kinerja Karyawan PT. Telekomunikasi Indonesia, Tbk Medan - Endang Haryati; Yuni Arti Maysaroh Pane (Faculty of Psychology, Universitas Medan Area, 2018)
This study aims to determine how much influence and relationship between office layout on employee performance at PT Telekomunikasi Indonesia, Tbk Medan. The population is 20 people and uses saturated samples. Data collection using questionnaire method tested with several methods of data analysis. The results of this study proved by testing the hypothesis that is: Test Validity and Reliability, Test T, Coefficient R and Coefficient R2 and Simple Linear Regression Analysis that indicates that the influence between office layout on employee performance. Based on Simple Linear Regression Analysis obtained equation Y = 16,638 + 0,684X, and if assumed every increase of office layout for unit then will improve employee performance equal to 0,684. Based on the analysis of product moment correlation obtained both variables have a strong relationship. Based on the analysis of determination, between office layout on employee performance of 41.0% means that the office spatial has an influence on the performance of 41.0%, while the remaining is 59.0% explained by other variables not discussed in this study. Based on the T-Test, it is explained that partially, the regression coefficient used is significant. In conclusion, that Ho is rejected and Ha accepted, which means there is a strong and significant influence between office layout on employee performance at PT. Telekomunikasi Indonesia, Tbk Medan.